2023
DOI: 10.25082/amler.2023.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Organizational evaluation and human recourses behavior

Abstract: Internal evaluation is inextricably linked to increasing the efficiency of a school unit. The collection and evaluation of data on the performance of the school unit, the school class, and student potential is critical to increasing the effectiveness of a school structure. The purpose of this study is to determine how significantly a school's efficiency increases at all levels of its organizational structure when self-evaluation is used. According to the study's findings, the implementation of assessment withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…International mobility teaching more commonly occurs during a week of interactive lectures and workshops on digital and non-digital environments to allow participants to develop functional competencies during their international careers (Mikhaylov, 2014;Stoltenberg et al, 2017). Apart from the students, educators can benefit from such international events to enhance their digital competencies (Vlachoudi et al, 2023), learn new methodologies regarding teaching practices and share knowledge and experiences with colleagues from other countries (Ciftci & Karaman, 2018;Withers et al, 2019). Additionally, conducting these events in a hybrid way and focusing on improving their digital competencies is paramount to both teachers and students as the high cost of traveling to such venues, especially if they are on different continents, can be discouraging to carry out (Jacobs et al, 2014;Schartner, 2016).…”
Section: International Mobility and Digital Competenciesmentioning
confidence: 99%
“…International mobility teaching more commonly occurs during a week of interactive lectures and workshops on digital and non-digital environments to allow participants to develop functional competencies during their international careers (Mikhaylov, 2014;Stoltenberg et al, 2017). Apart from the students, educators can benefit from such international events to enhance their digital competencies (Vlachoudi et al, 2023), learn new methodologies regarding teaching practices and share knowledge and experiences with colleagues from other countries (Ciftci & Karaman, 2018;Withers et al, 2019). Additionally, conducting these events in a hybrid way and focusing on improving their digital competencies is paramount to both teachers and students as the high cost of traveling to such venues, especially if they are on different continents, can be discouraging to carry out (Jacobs et al, 2014;Schartner, 2016).…”
Section: International Mobility and Digital Competenciesmentioning
confidence: 99%
“…As a result, they may be unable to cope and drop out of school (Pineda et al, 2022), leading to more sociocultural and psychological challenges. However, Vlachoudi et al (2023) posit that self-evaluation can lead to positive learning outcomes for students, and the results from such evaluation can improve lesson planning and design, which eventually helps the students' performance. Universities admitting international students can utilize organizational evaluation to combat these academic challenges.…”
Section: Academic Challengesmentioning
confidence: 99%
“…A preliminary observation is that there is a lack of research studies in this area that utilize a unified, ready-to-use model. Therefore, researchers must make an independent effort to develop specific questionnaires tailored to the case under investigation [37]. Having said that, the literature review stage was followed by a team discussion to determine and predefine the dependent variables for this study, as shown in Table 2.…”
Section: Fig 3 Gender Distribution Of Participants For the Experiment...mentioning
confidence: 99%